The red pyramid - Riordan,Rick (Kane Chronicles Graphic Novel ; bk. 1., 2013)
Carter and Sadie Kane's dad is a brilliant Egyptologist with a secret plan that goes horribly wrong. An explosion shatters the ancient Rosetta Stone and unleashes Set, the evil god of chaos ... Set imprisons Dr Kane in a golden coffin, and Carter and Sadie have to run for their lives. To save their dad, they must embark on a terrifying quest from Cairo and Paris to the American South-west and discover the truth about their family's connection to the House of Life: an Egyptian temple of magic that has existed fro thousands of years.